Gender Representation in English Textbook for 4th Grade Entitled Student’s Book My Next Word for Elementary School (Conference on English Language Teaching, 2023)
This study was aimed to investigate gender representation in an English Textbook entitledStudent’s Book My Next Words for Elementary School which published by The Republicof Indonesia’s Ministry of Education and Culture in 2021. Porecca’ (1984) frameworkwas adopted for analyzing the female and male representation in the English textbook:omission (the ratio of females to males) in texts and illustrations, firstness, occupationalvisibility, noun, masculine generic construction, and adjective. The visibility of genderimbalance was found in the textbook. The number of visibility data depicted that malewas higher than female. For social dominance was not found in the textbook. However,the variant of firstness, occupation, noun, masculine generic, and adjective for males arevarier than for females. Some stereotypes were found such as cooking for females’ activityand the breadwinner role for males. A limitation of the study is that it focuses on onetextbook only. Thus, this study can’t be generalized. For this purpose, another study witha larger sample would be required a deeper analysis of the picture of the EFL textbook.